2014
DOI: 10.1172/jci72051
|View full text |Cite
|
Sign up to set email alerts
|

An AXL/LRP-1/RANBP9 complex mediates DC efferocytosis and antigen cross-presentation in vivo

Abstract: The phagocytosis of apoptotic cells (ACs), or efferocytosis, by DCs is critical for self-tolerance and host defense. Although many efferocytosis-associated receptors have been described in vitro, the functionality of these receptors in vivo has not been explored in depth. Using a spleen efferocytosis assay and targeted genetic deletion in mice, we identified a multiprotein complex -composed of the receptor tyrosine kinase AXL, LDL receptorrelated protein-1 (LRP-1), and RAN-binding protein 9 (RANBP9) -that medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 55 publications
4
97
0
1
Order By: Relevance
“…Although we previously demonstrated that TNF receptor-1 (TNFR1) is increased in LRP1-deficient fibroblasts (12,42), TNFR1 regulation does not provide a straightforward explanation for the activity of LRP1 ligands. LRP1 demonstrates other important activities in macrophages that may be critical in tissue injury and the inflammatory response, including its function in phagocytosis of large particles (12), efferocytosis (15,43), and in regulating transforming growth factor-β (44). LRP1 also is involved in antigen presentation in support of adaptive immunity (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Although we previously demonstrated that TNF receptor-1 (TNFR1) is increased in LRP1-deficient fibroblasts (12,42), TNFR1 regulation does not provide a straightforward explanation for the activity of LRP1 ligands. LRP1 demonstrates other important activities in macrophages that may be critical in tissue injury and the inflammatory response, including its function in phagocytosis of large particles (12), efferocytosis (15,43), and in regulating transforming growth factor-β (44). LRP1 also is involved in antigen presentation in support of adaptive immunity (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Axl-mediated phagocytosis has previously been described to occur mainly in dendritic cells (25,61) and specifically under pro-inflammatory conditions (62), whereas Mer in both circulating and tissue-resident macrophages was suggested to contribute to homeostatic apoptotic clearance under tolerogenic settings. As the PMPs represent a large part of circulating MPs even under basal conditions, their phagocytic uptake could be expected to occur in a constantly ongoing manner resembling homeostatic Mer-dependent phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tabas’s laboratory showed that Axl −/− mice were in fact more susceptible to herpes simplex virus (HSV)-1 infection in vivo (160). This phenotype was ascribed to the reduced capacity of Axl −/− DCs to cross-present viral antigens.…”
Section: Tams In Diseasesmentioning
confidence: 99%